Analisis Permasalahan Pemerintahan, Pengembangan Bumdes, Kemisikinan Masyarakat desa dan Solusi yang ditawarkan Melalui Edukasi Kepada Masyarakat dan Praktek Kuliah Lapangan - Marno Wance (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2022)
Field practice lectures conducted by lecturers of Government Science study program, FISIP University of Pattimura to the second semester students of the Government Fundamentals class A. A total of 44 students. The targets of field practice for second semester students are (1). Increase students' knowledge about actual issues related to village government problems and the development of Village Owned Enterprises (BUMDES). (2). Increase student knowledge about Bumdes management and settlement models that can be carried out by the Village Government (Pemdes). (3). Increasing students' knowledge of understanding the strength of Bumdes' position as a training ground and developing democracy in a country's life. The field practice method is carried out in stages, namely (1). The survey stages include an initial assessment to the Financial and Development Supervisory Agency (BPKP) of Maluku Province to become one of the FGD resource persons, compiling materials and activity times (2). The implementation stages are activities carried out in Study Room 10 FISIP campus, Pattimura University, Focus Grub Discussion (FGD), problem analysis of Maluku Village Owned Enterprises (Bumdes). The field practicum used an approach, namely the training method and FGD for FISIP students, Pattimura University. The primary data carried out is a literature review and analysis of students' understanding of the discussion. The findings obtained are (1) the Realization of Village Funds (DD) has increased and can facilitate development programs and village community empowerment. (2). The distribution of village funds has the impact of reducing the poverty rate from 2014-2019, which has decreased by 1.32 percent. (3). The factors that become problems in the management of Bumdes in Maluku are (1). Extremely poor (2). Dependence on Central Government Transfer Funds. (3). Natural Resources Potential Not yet managed optimally. (4). Village Owned Enterprises (Bumdes) have not operated as they should. (5). The King/To the State Village Hasn't Been an Economic Driver. (6). Misuse of Village Funds